A techno-commercial review on grid connected photovoltaic system. (January 2018) - Chatterjee, Shantanu; Kumar, Prashant; Chatterjee, Saibal
Abstract: Owing to rapid depletion of fossil fuels and environmental hazard, different non-conventional sources of energy like wind, geothermal, nuclear, photovoltaic etc, have been taken into consideration for power generation. Environmental familiarness, reduced installation cost, improved power quality, abundant availability of source makes photovoltaic based distributed generation as one of the most popular alternative source of energy production. Improvement in power electronics technology makes synchronization of PV system with grid more viable. Power output from the PV module changes continuously with time depending upon the climatic condition. In order to get maximum output from the PV system different types of MPPT algorithm present in literature are studied and improvement proposed are described in this paper. Furthermore, different types of inverter topologies along with different grid synchronization technique and PWM topologies used to connect the PV system with the 3-phase AC grid are presented. In order to minimize the harmonic content of the inverter output, different types of filters used are presented in the proceeding section. Nextly different commonly used advanced islanding detection techniques for the safety purpose of PV based distribution generation system have been addressed and based on advantages and limitation of anti-islanding techniques, a comparison table has been presented. Afterward based on parameters like input, output voltage & current, MPP range, used standards etc, a comparison table between different commercially available grid tied PV inverters are presented in this paper. Finally, drawbacks of the prevailing grid connected PV system have been discussed.